Clinico-pathological investigations of Rasmussen encephalitis suggest multifocal disease progression and associated focal cortical dysplasia - Wang, Dandan; Blümcke, Ingmar; Gui, Qiuping; Zhou, Wenjing; Zuo, Huancong; Lin, Jiuluan; Luo, Yang (Epileptic Disorders, 2013)
Rasmussen encephalitis is a devastating neurological disorder characterised by seizures, brain inflammation, and progressive hemispheric atrophy. The objective of the current study was to systematically characterise patterns of structural lesions in children with Rasmussen encephalitis, referred for modified anatomical hemispherectomy at the Tsinghua University Epilepsy Center in Beijing. Seven consecutive patientswere investigated with a mean age at operation of 4.5 years, who suffered from medically intractable seizures for a mean of 1.6 years. Foci of abnormally increased T2 signal intensity were observed in all patients. With the exception of one child, all patients presented with progressive unilateral cerebral atrophy. FDG-PET imaging revealed extensive regions of hypometabolism within the affected cerebral hemisphere in 3 of 4 patients. Diagnosis of Rasmussen encephalitis was confirmed histologically, demonstrating CD68 positive microglial nodules, aswell as CD3 and CD8 positive T lymphocytes invading the cerebral parenchyma. An intriguing observation was the heterogenous distribution of patterns of lesions throughout the affected hemisphere, suggesting multifocal manifestation and distinct sequences of disease progression, from discrete foci of inflammatory infiltrates (stage 1) to extensive cortical destruction (stage 4). Atypical hippocampal sclerosis (HS), with neuronal cell loss affecting most prominently the CA4 region (HS type 3 or end folium sclerosis), was evident in 5 of 7 cases. Four hippocampi also showed chronic inflammation. In addition, we observed associated focal cortical dysplasia (FCD; ILAE type IIId) in 4 of 7 children, supporting the concept of acquired and postmigratory FCD pathomechanisms. Postsurgical seizure freedom was achieved in all children with a mean follow-up period of 2.7 years and continuous antiepileptic medication.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Dysplasia; Epilepsy; Inflammation; Neuropathology; Seizures